2022
DOI: 10.3389/fcvm.2022.988619
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hemi- vs. total arch replacement in acute type A aortic dissection: A systematic review and meta-analysis

Abstract: BackgroundAcute type A aortic dissections (ATAAD) pose a challenge to surgeons due to high mortality, and decision making regarding the appropriate procedure is controversial. This study compared the outcomes of hemiarch and total arch replacement for ATAAD.MethodsThe PubMed, Web of Science, Embase and Cochrane databases were searched for comparative studies on hemiarch versus total arch replacement that were published before May 1, 2022.ResultsWe included 23 observational studies with a total of 4,576 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…A meta‐analysis found that hemiarch replacement might have a lower early mortality rate, but the long‐term mortality rate was significantly higher in patients who underwent hemiarch replacement than in those underwent total arch surgery. 17 To adjust for the effects of other possible influencing factors, we conducted a univariable Cox regression analysis on all factors that may affect early mortality of patients, including total arch replacement. Factors with P <0.05 were included in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis found that hemiarch replacement might have a lower early mortality rate, but the long‐term mortality rate was significantly higher in patients who underwent hemiarch replacement than in those underwent total arch surgery. 17 To adjust for the effects of other possible influencing factors, we conducted a univariable Cox regression analysis on all factors that may affect early mortality of patients, including total arch replacement. Factors with P <0.05 were included in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is associated with a significant mortality risk. Patients often succumb to organ dysfunction resulting from aortic dissection rupture, pericardial tamponade, inadequate blood supply to the aortic branches (such as acute myocardial infarction and intestinal ischemic necrosis), acute renal insufficiency, and other complications ( 8 , 9 ). The mortality rate is approximately 50% within 48 h of onset and 70% within one month.…”
Section: Discussionmentioning
confidence: 99%
“…(14)(15)(16)(17)(18) However, while technology has advanced, there are still concerns regarding the technical complexity, duration of cardiopulmonary bypass (CPB), and circulatory arrest. Furthermore, there is evidence of wide variability in outcomes from center to center, and a recent meta-analysis suggested that EAR approaches may be associated with increased perioperative mortality (13)(14)(15)(16)(17)(18)(22)(23)(24). It is important to acknowledge these issues and work towards finding solutions that benefit all parties involved.…”
Section: Introductionmentioning
confidence: 99%